Keeping it Clean: A Healthy House - Mary N. Harrison; Amanda Griffin; Randall A. Cantrell (EDIS)
The way you clean and maintain your home will affect the health of your family, especially children. The incidence of children diagnosed with asthma is increasing. You can help make your home safe and healthy for your children by eliminating or controlling the risks outlined in this publication. This revised 2-page fact sheet was written by Mary N. Harrison, Amanda Griffin, and Randall A. Cantrell, and published by the UF Department of Family, Youth and Community Sciences, May 2014.